The cyclic triaxial test as tool to quantify coarse non-conventional materials response - Araújo, Nuno Miguel Faria (2011)
Sustainable waste management requires efficient dealing to protect landfill and reduce waste deposits. For that it becomes necessary to improve material characterization, using performance based tests, to estimate waste reuse as construction material. Several mechanical tests exist which make possible to use numerical tools to estimate reversible and irreversible behaviour of non-conventional coarse material, as industrial waste. From the available tests, the large-scale cyclic triaxial test is commonly used since it is the simple one to implement and allows the study of the irreversible behaviour, an import factor for materials to be used in roadway and railway infrastructures. The large-scale cyclic triaxial test is an equipment that exists on several important laboratories, in Europe, USA and Asia. This paper describes a large cyclic triaxial test facility developed at Centre for Waste Valorisation (Campus of University of Minho), able to study coarse aggregates/waste materials with grain size particles up to 50 mm.